MP AutoCAD 2004 Companion : Essentials of AutoCAD Plus Solid Modeling - A. Leach James (America : Mc Graw Hill Technoloy Education, 2004)
AutoCAD 2004 Companion covers all features and capabilities of AutoCAD. The text is command-oriented so chapters are centered around groups of related commands. This feature makes the text very effective as a reference text. The chapters are structured in a practical/pedagogical sequence beginning with instruction in general procedures for using the computer interface, setting up and creating drawings, and then progressing to advanced features such as dimensioning, special drawing applications and AutoCAD features, three-dimensional modeling and rendering, and software customization.
AutoCAD 2004 Companion provides material typically covered in a one-semester AutoCAD course. It covers the essentials of 2D design and drafting as well as solid modeling. AutoCAD 2004 Companion can be used as a standalone AutoCAD text or in combination with other discipline-specific graphics texts such as Bertoline's Technical Graphics Communication or Fundamentals of Graphics Communication.
New AutoCAD 2004 coverage includes Qnew, Shadeplot, and Tool Palette, among other features.
Keywords: Autocad; Vẽ kỹ thuật; Computer Aided Design; Phần mềm thiết kế; Technical Drawing